Family Financial Management in Contemporary Premarital Guidance from the Perspective of Maqashid al-Shari‘ah - M. Ridha Rahmat Putra; Ezi Zul Hayati; M. Khairul Arwani (USRATY : Journal of Islamic Family Law, 2025)
This study aims to analyze the implementation of family financial management in contemporary premarital guidance and its relevance to the realization of a sakinah family from the perspective of maqashid al-shari‘ah. The background of this research stems from the increasing number of marital conflicts and divorces caused by poor financial literacy and economic instability among couples, highlighting the urgent need for premarital education that addresses financial issues. Employing a qualitative approach with a descriptive method, this research collects data through interviews, observations, and documentation at the Office of Religious Affairs (KUA) Tanjung Raya, which uniquely integrates family financial management into its premarital guidance program. The findings reveal that such integration significantly enhances the financial awareness and responsibility of prospective couples, reduces the potential for economic-based conflicts, and supports sustainable family welfare. The counseling model not only addresses practical financial challenges but also embodies the principles of maqashid al-shari‘ah by protecting religion, life, intellect, lineage, and wealth (hifzh al-din, al-nafs, al-‘aql, al-nasl, and al-mal). Therefore, this study concludes that family financial management in premarital guidance serves as a strategic and preventive instrument for realizing the objectives of Sharia and achieving a sakinah family in the modern context. Academically, this research contributes to the discourse on integrating financial literacy into Islamic family law and premarital education.